The Role of Rumination in University Students’ Mental Health: A Mediation Analysis of Depression and Anxiety - Nisaul Maghfiroh; Ernasiwi Astri Oktavilia; Arfi Nurul Hidayah; Isran Kamal; Hajid Rahmadianto Mardihusodo; Muhammad Zaenuri Syamsu Hidayat (Medical and Health Journal, 2026)
This study examined the relationship between rumination and mental health among university students by testing the mediating roles of depression and anxiety. Rumination refers to a repetitive and passive focus on negative experiences and emotions that may influence psychological functioning. A quantitative correlational design was employed. A total of 113 students completed the Ruminative Response Scale (RRS), Beck Depression Inventory-II (BDI-II), Beck Anxiety Inventory (BAI), and General Health Questionnaire (GHQ-12). Parallel mediation analysis indicated that rumination significantly predicted depression (β = .6197, p < .001) and anxiety (β = .5830, p < .001). Depression significantly predicted mental health (β = .2893, p = .025), whereas anxiety was not a significant predictor (β = .1186, p = .343). The direct effect of rumination on mental health was not significant (β = −.0940, p = .427), nor was the total effect (β = .1544, p = .098). However, the indirect effect through depression was significant (β = .1793, p = .031; 95% CI [.00464, .0957]), whereas the indirect path through anxiety was not significant (β = .0692, p = .347). These findings indicate that depression fully mediates the relationship between rumination and mental health. Thus, the influence of rumination on students’ mental health primarily operates through increased depressive symptoms.